2022
DOI: 10.1155/2022/1399618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of AlN-SiC Nanoparticle Reinforcement on the Mechanical Behavior of Al 6061-Based Hybrid Composite Developed by the Stir Casting Route

Abstract: The enhancement of composites’ mechanical characteristics (tensile, compressive, and hardness) is a constant demand for technological advancement. The stir casting process is used to make the hybrid aluminium alloy metal matrix composites Al 6061-SiC-AlN in our present study. To create mechanical qualities such as tensile, compressive, and hardness, silicon carbide and aluminium nitride (both 3% and 6%) were utilized as the reinforcement. The tensile strength, compressive strength, and hardness of the Al 6061-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The study confirmed improved thermal and corrosion resistance, marking significant potential for lightweight, high-strength material applications in demanding environments. 10) investigated the mechanical properties of Al 6061 hybrid composites reinforced with AlN-SiC nanoparticles using stir casting. The study found that adding 3% and 6% of AlN and SiC nanoparticles significantly improved the composites' tensile strength, compressive strength, and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The study confirmed improved thermal and corrosion resistance, marking significant potential for lightweight, high-strength material applications in demanding environments. 10) investigated the mechanical properties of Al 6061 hybrid composites reinforced with AlN-SiC nanoparticles using stir casting. The study found that adding 3% and 6% of AlN and SiC nanoparticles significantly improved the composites' tensile strength, compressive strength, and hardness.…”
Section: Introductionmentioning
confidence: 99%